Relaxation Training as a Reading Remediation Tool for School-Aged Children - Culbertson, Frances M.; Wille, Craig (Canadian Journal of Counselling and Psychotherapy, 2012)
This study sought to evaluate the effectiveness of a relatively short-term programof relaxation training in producing changes in elementary students in terms of attention-related skills associated with reading tasks in the classroom. Evaluation of change was measured by change in experimental variables under examination as well as subjective evaluations of change coming from students, parents, as well asexaminations of on-going work production and style.